2020
DOI: 10.1111/acer.14399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Correlates of Topiramate and GRIK1 rs2832407 Genotype in Pluripotent Stem Cell–Derived Neural Cultures

Abstract: There is growing evidence that the anticonvulsant topiramate is efficacious in reducing alcohol consumption.Further, an intronic single nucleotide polymorphism (rs2832407, C ! A) in the GRIK1 gene, which encodes the GluK1 subunit of the excitatory kainate receptor, predicted topiramate's effectiveness in reducing heavy drinking in a clinical trial. In the current study, we differentiated a total of 22 induced pluripotent stem cell (iPSCs) lines characterized by GRIK1 rs2832407 genotype (10 A/A and 12 C/C) into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Mature cultures, operationally defined as 12 weeks post neural cell plating, contain a mixture of neurons and glial cells. With this protocol, approximately 50% of cells show immunostaining for the glutamatergic neuron transcription factor TBR1 and 25% for GABA‐ergic markers (Fink et al, 2017; Lieberman et al, 2020; Lieberman, Kranzler, Levine, & Covault, 2018). Neurons in these cultures demonstrate spontaneous synaptic activity, functional ionotropic GABA A and glutamatergic receptors, and an ability to generate trains of action potentials in response to current injection (Lieberman et al, 2012) Fink et al, 2017; Lieberman et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature cultures, operationally defined as 12 weeks post neural cell plating, contain a mixture of neurons and glial cells. With this protocol, approximately 50% of cells show immunostaining for the glutamatergic neuron transcription factor TBR1 and 25% for GABA‐ergic markers (Fink et al, 2017; Lieberman et al, 2020; Lieberman, Kranzler, Levine, & Covault, 2018). Neurons in these cultures demonstrate spontaneous synaptic activity, functional ionotropic GABA A and glutamatergic receptors, and an ability to generate trains of action potentials in response to current injection (Lieberman et al, 2012) Fink et al, 2017; Lieberman et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With this protocol, approximately 50% of cells show immunostaining for the glutamatergic neuron transcription factor TBR1 and 25% for GABA‐ergic markers (Fink et al, 2017; Lieberman et al, 2020; Lieberman, Kranzler, Levine, & Covault, 2018). Neurons in these cultures demonstrate spontaneous synaptic activity, functional ionotropic GABA A and glutamatergic receptors, and an ability to generate trains of action potentials in response to current injection (Lieberman et al, 2012) Fink et al, 2017; Lieberman et al, 2020). A comparison of transcriptome profiles for human iPSC‐derived forebrain lineage neural cultures and human postmortem brain tissue indicated that 12‐week iPSC‐derived neural cultures are most similar to that of first trimester forebrain tissue (Brennand et al, 2015; Mariani et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is associated with behavioral, cognitive, and physiological symptoms, including a strong need to consume alcohol, decreased control over use, use despite harmful consequences, social impairment, risky use patterns, and physiologic tolerance and withdrawal [ 1 , 2 , 3 ]. AUD is the most commonly diagnosed addiction.…”
Section: Introductionmentioning
confidence: 99%